Transformasi Digital dalam Manajemen Pendidikan Islam: Menavigasi Perubahan Teknologi dan Menjaga Nilai-Nilai Islam - Zulfatul Wasilah; Ahmad Mahfud (Abdurrauf Journal of Education and Islamic Studies, 2026)
The rapid development of digital technology has significantly transformed educational governance, including within Islamic educational institutions that are required to adapt to technological change while maintaining their Islamic identity and values. This study examines the dynamics of digital transformation in Islamic education management by focusing on the structural and cultural challenges emerging from the process of educational digitalization. The objective of this research is to analyze the major challenges faced by Islamic education management in the digital era and to formulate strategic directions for integrating technology while remaining grounded in Islamic values. This research employs a qualitative approach using a library research method through critical review and synthesis of relevant national and international scholarly literature, including reputable journal articles, academic books, and research reports. Data were analyzed using conceptual analysis through processes of identification, categorization, and synthesis of key concepts related to Islamic education management and digital transformation. The findings reveal that the digitalization of Islamic education management encounters four major challenges: limited technological infrastructure, low levels of digital literacy and competency among human resources, organizational cultural resistance to change, and concerns regarding the preservation of Islamic values in the process of educational modernization. At the same time, digitalization offers strategic opportunities to improve managerial efficiency, expand access to education, and develop technology-based and hybrid learning models. Therefore, digital transformation in Islamic education requires adaptive leadership, continuous capacity building, and the development of value-based management strategies to ensure that technological integration operates effectively, sustainably, and in alignment with the principles of Islamic education. [Perkembangan teknologi digital telah mendorong transformasi signifikan dalam tata kelola pendidikan, termasuk pada lembaga pendidikan Islam yang dihadapkan pada tuntutan adaptasi teknologi tanpa mengabaikan nilai-nilai keislaman sebagai fondasi institusional. Penelitian ini mengkaji dinamika transformasi digital dalam manajemen pendidikan Islam dengan menyoroti tantangan struktural dan kultural yang muncul dalam proses digitalisasi pendidikan. Tujuan penelitian ini adalah menganalisis tantangan utama yang dihadapi manajemen pendidikan Islam di era digital serta merumuskan arah strategis integrasi teknologi yang tetap berlandaskan nilai-nilai Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan melalui penelaahan kritis dan sintesis terhadap berbagai sumber literatur ilmiah yang relevan, termasuk artikel jurnal bereputasi, buku akademik, dan laporan penelitian. Analisis data dilakukan melalui analisis konseptual dengan tahapan identifikasi, kategorisasi, dan sintesis konsep-konsep kunci yang berkaitan dengan manajemen pendidikan Islam dan transformasi digital. Hasil penelitian menunjukkan bahwa digitalisasi dalam manajemen pendidikan Islam menghadapi empat tantangan utama, yaitu keterbatasan infrastruktur teknologi, rendahnya literasi dan kompetensi digital sumber daya manusia, resistensi budaya organisasi terhadap perubahan, serta kekhawatiran terhadap potensi erosi nilai-nilai Islam dalam proses modernisasi pendidikan. Di sisi lain, digitalisasi juga menghadirkan peluang strategis dalam meningkatkan efisiensi manajerial, memperluas akses pendidikan, serta mengembangkan model pembelajaran berbasis teknologi dan pembelajaran hibrida. Oleh karena itu, transformasi digital dalam pendidikan Islam memerlukan kepemimpinan yang adaptif, penguatan kapasitas sumber daya manusia, serta pengembangan model manajemen berbasis nilai agar integrasi teknologi dapat berlangsung secara efektif, berkelanjutan, dan tetap selaras dengan prinsip-prinsip pendidikan Islam.]